Dropout of Newly Diagnosed Glaucoma Patient from Follow-up Schedule - Md Abdus Salam Mostak Ahmed, Anis-ur-Rehman, Jamsed Faridi S.M Enamul Haque, Mukti Rani Mitra (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the impact of verbal counseling alone and verbal with structured written counseling in prevention of drop out of glaucoma patients from follow-up schedule. Study Design: Descriptive study. Place and duration of study: Green Eye Hospital Dhaka, Bangladesh for 18 months, from July 2015 to December 2016. Conclusion: Drop out during follow up in newly diagnosed glaucoma patients is less if they are given written brochures with verbal counselling. Drop out of elderly glaucoma patients is lesser than the younger age group. Key words: Glaucoma, glaucoma counseling, intra ocular pressure